Development of Knowledge, Attitude and Practice Questionnaire of Parents towards Vaccination: Process, Challenges and Solutions - Sebastian, Juny; Parthasarathi, Gurumurthy; Ravi, Mandyam Dhati (Indian Journal of Pharmacy Practice)
Objectives: This study aimed to develop and validate a questionnaire to observe the knowledge, attitude and practice of parents towards vaccination. Methods: The questionnaire was developed based on an extensive literature review and experts’ opinion. The questionnaire was then subjected for validation and translated to the local vernacular from English. Cronbach’s alpha and Sperman’s rank coefficient was used to estimate the internal consistency of the questions in the questionnaire and test –retest reliability of the questionnaire respectively. Results: The overall content validity score and the item content validity index (I-CVI) of the prepared questionnaire was 3.83 and 95.5% respectively. The internal consistency of the questionnaire measured using Cronbach’salpha was found 0.89. The mean + standard deviation of the KAP scores for test group and retest group was 37.5 + 6.53 and 37.9 + 6.063 respectively. The calculated Sperman’s rank correlation coefficient value was 0.957 (p<0.001). Conclusion: The questionnaire is acceptable and the relevance was high among all the four parameters (97%) of the content validity index. The prepared questionnaire showed high reliability and stability between KAP scores of the test and retest. The Kannada questionnaire is simple and easy to use but the time taken to complete the questionnaire is a limitation of the study.
Keywords: Knowledge; Attitude and Practice (KAP); Content Validity; Validation of Questionnaire; Immunization